INNOVATIVE SOLUTIONS FOR LIGHTING ONLINE PROJECTS IN THE DEVELOPMENT OF CULTURAL TOURISM IN RUSSIA (BASED ON THE ANALYSIS OF FOREIGN AND DOMESTIC MUSEUMS) - Muxamedova Munisa Sabirovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article explains innovative solutions for online projects in the development of cultural tourism during the coranavirus pandemic based on the analysis of foreign and domestic museums. Opportunities for developing online tourism in the local tourism system of Uzbekistan were also highlighted.